The Berlin apartment - Turnbull, Bryn (Mira, 2024)
"Uli and Lise, newly engaged, are separated by the Berlin Wall and over the course of the next twenty-eight years, as they bear witness to the realities of life on either side, they defy the imposed separation by embracing a love that cannot be broken.